Plasticizer For Liquid Polymeric Membrane Of Ion Selective Electrode Based On Thiazole Derivatives As Ionophore - Noor Wahidah Zainol Jamil; Muhd Zu Azhan Yahya; Noor Azilah Mohd Kasim; Juliana Jumal (UR Publishers, 2024)
Non-Indexed Publication